Seasonal changes in the incidence of Escherichia coli bloodstream infection: variation with region and place of onset. (October 2015) - Deeny, S.R.; van Kleef, E.; Bou-Antoun, S.; Hope, R.J.; Robotham, J.V.
Abstract: Previous research has shown that Escherichia coli infection rates peak in the summer; however, to date there has been no investigation as to whether this is seen in both hospital and community-onset cases, and how this differs across regions. We investigated and quantified E. coli bloodstream infection (BSI) seasonality. A generalized additive Poisson model was fitted to mandatory E. coli BSI surveillance data reported in England. There was no impact of seasonality in hospital-onset cases; however, for the community-onset cases, there was statistically significant seasonal variation over time nationally. When examined regionally, seasonality was significant in the North of England only. This variation resulted in an absolute increase of 0.06 (95% CI 0.02–0.1) cases above the mean (3.25) in each hospital trust for each week of the peak summer season, and a decrease of (−) 0.07 (95% CI –0.1 to –0.03) in the autumn. We estimate that fewer than one hospital bed-day per week per hospital is lost because of seasonal increases during the summer. Our findings highlight the need to understand the distinct community and hospital dynamics of E. coli BSI, and to explore the regional differences driving the variation in incidence, in order to design and implement effective control measures.